Intermediate CAG repeat expansion in the ATXN2 gene is a unique genetic risk factor for ALS--a systematic review and meta-analysis of observational studies. - Ming-Dong Wang; James Gomes; Neil R Cashman; Julian Little; Daniel Krewski (PLoS ONE, 2014)
Amyotrophic lateral sclerosis (ALS) is a rare degenerative condition of the motor neurons. Over 10% of ALS cases are linked to monogenic mutations, with the remainder thought to be due to other risk factors, including environmental factors, genetic polymorphisms, and possibly gene-environmental interactions. We examined the association between ALS and an intermediate CAG repeat expansion in the ATXN2 gene using a meta-analytic approach. Observational studies were searched with relevant disease and gene terms from MEDLINE, EMBASE, and PsycINFO from January 2010 through to January 2014. All identified articles were screened using disease terms, gene terms, population information, and CAG repeat information according to PRISMA guidelines. The final list of 17 articles was further evaluated based on the study location, time period, and authors to exclude multiple usage of the same study populations: 13 relevant articles were retained for this study. The range 30-33 CAG repeats in the ATXN2 gene was most strongly associated with ALS. The meta-analysis revealed that the presence of an intermediate CAG repeat (30-33) in the ATXN2 gene was associated with an increased risk of ALS [odds ratio (OR) = 4.44, 95%CI: 2.91-6.76)] in Caucasian ALS patients. There was no significant difference in the association of this CAG intermediate repeat expansion in the ATXN2 gene between familial ALS cases (OR = 3.59, 1.58-8.17) and sporadic ALS cases (OR = 3.16, 1.88-5.32). These results indicate that the presence of intermediate CAG repeat expansion in the ATXN2 gene is a specific genetic risk factor for ALS, unlike monogenic mutations with an autosomal dominant transmission mode, which cause a more severe phenotype of ALS, with a higher prevalence in familial ALS.